DEVELOPMENT OF NATIONAL LEGAL DEVELOPMENT IN THE FRAMEWORK OF HEART TRANSPLANTATION IN INDONESIA - Yasarman (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Responsive Pancasila law that nurtures and protects can be realized if the law is able to provide a sense of security and peace to the life of the nation and state and to the people as a whole. The law becomes a place of protection and protection for the people from actions that threaten and destroy the sense of security, peace and human rights. Just law based on Pancasila is a formulation of justice that is carried out in Indonesian society, which is justice which emphasizes the balance between rights and obligations, namely the right to enjoy the results of development with the obligations of darma and service. With this formulation of justice, the development of national law in the constitutional state of Pancasila basically aims to protect: (1) the entire Indonesian nation, (2) all Indonesian blood, (3) the ideals and goals of the Indonesian nation, (4) Indonesian society and individuals (5) soul, individual freedom, honor, and property, (6) implementation of development (law must function as a means of supporting the development of modernization and comprehensive development).